Effect of metoclopramide on transport in the small intestine of the dog. Issue 12 (December 1969) - Tinker, John; Cox, Alan G.
Abstract : A method is described for the simultaneous measurement of flow rate, mean transit time, and volume of the intestine during the transport of fluid through a segment of the small intestine of the dog. Using this method, the effect of metoclopramide on motility of the small bowel was assessed. The drug resulted in a decrease in transit time and volume in the test segment of bowel while the flow rate remained constant. This finding suggests that metoclopramide-stimulated contraction of intestinal smooth muscle.